Concurrea Processing in Microsoft Dynamics CRM Using Python (International Journal of Innovative Research in Computer Science & Technology, 2023)
The realm of Customer Relationship  Management (CRM) has seen significant improvements  with the integration of automation and data analytics.  Python, known for its robust data manipulation libraries,  offers a seamless experience for handling data in Microsoft  Dynamics CRM. This paper aims to serve as a  comprehensive guide on how Python can be employed to  perform CRUD operations— Read, Update, Insert—on data  in Microsoft Dynamics CRM. We delve into the intricacies  of using Python's 'requests' library for API calls and  'concurrent futures' for parallel processing, thereby  optimizing data manipulation tasks. The paper also presents  a performance evaluation showcasing the efficiency gains  achieved through these methods. Furthermore, the paper  highlights the challenges associated with large-scale data  management in CRM systems and proposes Python-based  solutions as a scalable and effective approach. The paper  concludes with a discussion on the scope of this approach in  the broader context of CRM data analytics and automation.  The methods and findings presented herein are expected to  be of particular interest to data engineers, software  developers, and CRM administrators.
Keywords: Concurrent; Data; Dataverse; Dynamics; Parellel; PowerApps; Python